2021
DOI: 10.7759/cureus.18006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Clinical, Pathological and Prognostic Features of Coexistent Membranous and IgA Nephropathy in a Series of 13 Patients at a Tertiary Care Hospital

Abstract: BackgroundMembranous nephropathy (MN) and immunoglobulin A nephropathy (IgAN) are although two different entities, yet can rarely coexist. There is not much data available on this coexistent disorder, specifically with regard to the treatment modality and outcome. Here, we analyse in detail, retrospectively, 13 cases of coexistent IgA and membranous nephropathy (IgA-MN). MethodsRenal biopsy data of 1084 diagnosed cases of either membranous or IgA nephropathy was obtained from March 2015 till March 2021. Out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Our previous study reported that one third of patients who were PLA2R and THSD7A negative were NELL-1 positive [14]. In our study, patients with PMN/IgAN had a lower frequency of serum anti-PLA2R antibody and glomerular PLA2R positivity, consistent with other research findings [7,15]. Despite that the positive rates of glomerular PLA2R were lower in the PMN /IgAN group, glomerular IgG4 positive rates were similar.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our previous study reported that one third of patients who were PLA2R and THSD7A negative were NELL-1 positive [14]. In our study, patients with PMN/IgAN had a lower frequency of serum anti-PLA2R antibody and glomerular PLA2R positivity, consistent with other research findings [7,15]. Despite that the positive rates of glomerular PLA2R were lower in the PMN /IgAN group, glomerular IgG4 positive rates were similar.…”
Section: Discussionsupporting
confidence: 91%
“…There has been much controversy. Previous literature has reported that PMN and IgAN may occur in the same patient at an interval of several years [17,18] or on the occurrence of superimposed MN on a background of preexisting IgAN [7,19]. Conclusions are unclear.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations